Long-term outcomes of transcatheter Potts shunt in children with suprasystemic pulmonary arterial hypertension - Haddad, Raymond N.; Levy, Maryline; Szezepanski, Isabelle; Malekzadeh-Milani, Sophie; Bonnet, Damien (Frontiers in Cardiovascular Medicine, 2022)
Background Transcatheter Potts shunt (TPS) is a palliation alternative for children with severe pulmonary arterial hypertension (PAH). Debates on the long-term outcomes remain unsolved. Objectives To evaluate long-term clinical and procedural outcomes of TPS intervention. Methods Single-center retrospective data review of children with severe PAH who had TPS between 2009 and 2018. Patients who died per-operatively and early post-procedure were excluded. Long-term outcomes of survivors were evaluated. Results Out of 13 identified patients (53.8% males), 7 had endovascular stenting of probe/patent arterial ducts, while 6 individuals had aorta-to-pulmonary radiofrequency perforation and covered stent placement. Compared to baseline, the overall clinical condition significantly improved at discharge (p < 0.001) and stayed better at the last visit (p < 0.05) despite frequent clinical worsening events across follow-up. Improvement in functional class across follow-up was significant (p < 0.001). There was, however, no significant improvement in other disease markers (TPASE, 6MWD z-scores, and NT-proBNP levels) or reduction in PAH medications. The median follow-up was 77.4 months (IQR, 70.7–113.4). Survival was 100% at 1 year and 92.3% at 6 years. Freedom from reinterventions was 77% at 1 year and 21% at 6 years. Nine (69.2%) patients had stent reinterventions at a median of 25 months (IQR, 9.5–56) postoperative. Balloon dilatation and restenting were performed in 53.8% and 46.2% of patients, respectively. High-pressure post-dilatation of implanted stents was performed in 53.8% of patients during TPS intervention for incomplete stent expansion and/or residual pressure gradient and was associated with higher rates of reinterventions (p = 0.021). Stent malfunctioning was present in 46.2% of patients at last follow-up. Two patients are listed for heart-lung transplantation. Conclusion Survivors of TPS procedures experience significant improvement in functional class that can be durable. Clinical worsening and stent malfunctioning are frequent morbid events indicating recurrent transcatheter reinterventions throughout follow-up. Six-year survival is, however, satisfactory.